A Cost and Quality Analysis of Utilizing a Rectal Catheter for Medication Administration in End-of-Life Symptom Management. (3rd July 2018) - Latuga, Natalie M.; Gordon, Mary; Farwell, Paula; Farrell, Megan O.
Abstract: Technology that can improve the ability to provide quick symptom control while decreasing the cost and burden of care could help hospice agencies deal with current hospice industry challenges. This paper describes how the use of a new rectal medication delivery technology at a large hospice in western New York has improved patient care and nursing efficiency while at the same time decreasing the cost of care.